Form of Mandate as a Message in Folklore - Yusni Khairul Amri; Dian Marisha Putri; Bambang Panca Saputra (Matondang Journal, 2022)
Folklore often reflects the creativity of traditional communities while still holding fast to tradition as a manifestation of creativity that lives and is passed down from generation to generation. Thus, folklore stories remain oriented towards values as a mandate with local ethnic content. The mandate as a value has always been a measure in determining truth and justice that comes from the content of religion, logic, and norms that apply in society. Interpreting values in folklore by interpreting a behavioral tendency that starts from psychological symptoms such as: desires, motives, attitudes, needs, and beliefs, so that the values of folklore can be used as parametric values of education, religion. The form of the mandate as values in folklore stories can educate in taking lessons as well as role models that are worthy of being guided and then used as examples of bad and bad behavior not to be imitated like a mother's love for her child who sincerely and selflessly forgives her child. The mandate as a value in Karo folklore is biased such as: a) the mandate to forgive, b) the mandate to obey parents, c) the mandate to keep promises, d) the mandate to be patient, e) the mandate not to be arrogant and arrogant, f) the mandate to be humble.